Ngaku Indaok in Sitinjau Laut Community According to Maqashid Shari'ah Review - Nurul Izzati; Zainal Azwar (Journal of Law, Society, and Islamic Civilization, 2024)
This research aims to explain how the practice of "Ngaku Indaok" in Sitinjau laut Sub-district with the focus of Maqashid Syariah approach. The research method used is qualitative with data collection techniques through literature study and interviews with key informants from the local community. The results show that although different in implementation from legal child adoption, both Ngaku Indaok and child adoption reflect the aspirations of the Kerinci community to provide support and protection to children who need a more stable family environment. A holistic evaluation is required to safeguard Islamic values and the right to individual freedom while respecting local traditions, demonstrating the Kerinci community's efforts to harmonize traditions with values consistent with religious teachings and social norms. The affection and emotional support in Ngaku Indaok does not only focus on material aspects, but also creates educational and developmental opportunities for the child, reflecting its link to the preservation of wealth (hifdz mal) and the preservation of the intellect (hifdz aql). However, it is important to note that the biological mother is no longer called mother or anything similar after the child confesses indaok to another woman.